2022
DOI: 10.1007/s00520-022-06883-0
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the financial and psychological impact of employment disruption among caregivers of pediatric HSCT recipients: a mixed methods analysis

Abstract: Purpose Pediatric hematopoietic stem cell transplantation (HSCT) confers a substantial financial burden onto patients’ families. In addition to high direct medical costs, HSCTs typically require at least one caregiver to take time away from work or other responsibilities, often leading to reduced household income. Using mixed methods, we sought to understand the impact of pediatric HSCT on caregiver employment and financial need. Methods We surveyed caregivers of living… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…These findings in the context of our other work, 19 suggest that high treatment costs and prolonged inability to work when caring for recipients may put caregivers of HSCT recipients at risk of heightened severe financial burden.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…These findings in the context of our other work, 19 suggest that high treatment costs and prolonged inability to work when caring for recipients may put caregivers of HSCT recipients at risk of heightened severe financial burden.…”
Section: Discussionsupporting
confidence: 53%
“…Recommendations regarding employment policy are discussed in a prior publication from this study. 19 At the hospital level, caregivers recommended that proactive support be provided to them through social workers or navigators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior literature has shown that low‐income workers have lower work flexibility, 25 which could lead to greater work disruption and financial burden. In qualitative studies, workplace flexibility has been an important factor protecting against unwanted vocational change after cancer diagnosis 26,27 . Thus, we hypothesized that greater work flexibility is associated with higher income and less financial burden.…”
Section: Introductionmentioning
confidence: 99%
“…In qualitative studies, workplace flexibility has been an important factor protecting against unwanted vocational change after cancer diagnosis. 26,27 Thus, we hypothesized that greater work flexibility is associated with higher income and less financial burden.…”
mentioning
confidence: 99%